Pelatihan Pembuatan Sediaan Teh dari Bunga Rosella Ungu (Hibiscus sabdariffa L.) sebagai Antioksidan Alami di Desa Pondok - Novena Yety Lindawati; Nastiti Utami; Anita Mursiany; Disvana Mardiningtyas; Imelda Cantika Putri; Maria Neheria Kusuma; Oktavia Kharismawati Cahya Rahmadani (Universitas Muhammadiyah Semarang, 2026)
Purple roselle (Hibiscus sabdariffa L.) is a medicinal plant rich in anthocyanins and flavonoids, which function as natural antioxidants capable of neutralizing free radicals and preventing degenerative diseases. However, the community of Desa Pondok continues to use purple roselle sparingly, both for its health benefits and its economic potential. This community service program aimed to improve the knowledge and skills of PKK cadres and health volunteers in Desa Pondok in processing purple roselle into functional herbal tea. The program was conducted in four stages: a health education session on the benefits of roselle; training in the preparation of simplisia; a herbal tea-making workshop; and the introduction of simple digital marketing strategies. Evaluation was conducted through pre- and posttests and participant satisfaction questionnaires. The results showed a significant improvement in participants’ understanding, with the average pretest score of 57 rising to 96.67 in the posttest (p=0.000). Additionally, the level of community satisfaction with the overall implementation of the activity reached 97.88%, with an average satisfaction index of 4.89, indicating high satisfaction. The training not only equipped participants with technical skills but also opened opportunities for developing local herbal-based businesses. This activity proved effective in promoting the use of local natural resources and increasing community awareness of the importance of consuming natural antioxidants.